Indonesian Director’s Duty to Act in the Interest of the Company: Can Human Rights Due Diligence be Included? - Bunga Dita Rahma Cesaria (Mahadi: Indonesia Journal of Law, 2026)
Business is nowadays inseparable from the scrutiny of human rights protection measures. Among many instruments that ensure businesses are aligned with human rights protection is the United Nations Guiding Principle on Business and Human Rights (UNGP) which calls for corporate responsibility to respect human rights. One of the principles upheld by the UNGP is Human Rights Due Diligence (HRDD). The Indonesian government recently indicates that, in the renewal of the National Action Plan on Business and Human Rights, HRDD will become mandatory for companies. As the organ that has the duty to manage a company, board of directors will be the one responsible in ensuring that HRDD, when it becomes mandatory, is complied with. Using juridical normative legal research, this paper answers the question on how HRDD can become part of the director’s duty to act in the interest of the company. This paper argues that HRDD is a part of Indonesian director’s duty. Using corporate objective theory, this paper finds that maximizing stakeholder’s interest is a part of fulfilling company’s interest under Indonesian company law that is drafted with collectivism (asas kekeluargaan) in Pancasila. This paper intends to inform business actors on potential additional obligation of director’s duty in the future. It also wishes to inform Indonesian policymaker on potential challenges in the implementation of HRDD such as the broad scope of human rights violation, absence of clear procedures, and risk of more burden for micro, small and medium companies.